Protein, salt, and premix aspects of all-concentrate cattle finishing rations - Roth, G.M.; Smith, E.F.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station, 2011)
This test was designed to study the following aspects of all-concentrate rations: (1) salt, (2) supplemental protein (3) self-feeding a protein and premix combination (4) a pelleted premix compared to a mash form, and (5) a repeat trial of soybean meal versus urea as a supplemental protein source.
Keywords: Beef; Protein; Salt; Premix; Finishing rations